Nyāyenduśekharaḥ: navyanyāyanibandhaḥ - Śaṭhakopācārya; Tayaru, G. Amruthavalli; Penna, Madhusūdana (Bhārataratna Pāṃ. Vā. Kāṇe Saṃskr̥ta-Adhyayana-Kendram, 2023)
Essays composed with the chief objective of refuting the views of the Kevaladvatins regarding the concept of mithya and other.